Effect of Gardeniae Fructus Powder on Growth Performance, Antioxidant Capacity, Intestinal Barrier Function, and Colonic Microbiota of Weaned Piglets - Shilong Liu; Min Tian; Ming Ma; Yueqin Qiu; Jiaxi Tang; Jing Hou; Qi Lu; Chaoyang Tian; Guohao Ye; Li Wang; Kaiguo Gao; Shining Guo; et al. (Animals)
The present study aimed to explore the effect of GF powder on the growth performance, diarrhea rate, antioxidant and immune capacity, and intestinal health of weaned piglets. A total of 144 weaned piglets (8.29 ± 0.11 kg) at 21 d old were randomly assigned to four groups, with each treatment consisting of six replicate pens, with six piglets per pen, and each pen containing three barrows and three gilts. The piglets were fed a basal diet supplement with 0%, 0.4%, 0.6%, and 0.8% GF powder (n = 36). Our results indicated that compared with the basal diet, the F/G and diarrhea rate were remarkably decreased in the 0.8% GF group (p < 0.05). Serum biochemical parameters showed that supplementation with GF significantly increased the content of HDL-C (0.6 and 0.8% levels), IL-6 (0.8% level), IL-10 (0.4, 0.6, and 0.8% levels), Ig G (0.4% level), and Ig A (0.8% level) compared with the basal diet (p < 0.05). The index of antioxidant capacity showed that compared with a basal diet, supplementation with GF significantly decreased serum MDA content (0.4% and 0.8% levels) and jejunal and ileal MDA content (0.4%, 0.6%, and 0.8% levels) (p < 0.05). Additionally, compared with the basal diet, supplementation with GF significantly increased serum and ileal T-AOC content (0.4%, 0.6%, and 0.8% levels), serum T-SOD content (0.4% and 0.8% levels), ileal T-SOD content (0.4%, 0.6%, and 0.8% levels), CAT content (0.4%, 0.6%, and 0.8% levels), and jejunal GSH-Px content (0.8% level) (p < 0.05). The results of gene expression indicate that compared with the basal diet, supplementation with GF significantly increased Nrf 2 (0.4% level), NQO (0.4% level), SOD 1 (0.4% and 0.8% levels), and GCLC (0.4% level) and GCLM (0.8% level) abundance in jejunal mucosa; supplementation with GF significantly increased Nrf 2 (0.4%, 0.6%, and 0.8% levels), HO-1 (0.4% level), NQO (0.8% level), SOD 1 (0.4% and 0.8% levels), and GCLC (0.4% level) and GCLM (0.8% level) abundance in ileal mucosa (p < 0.05). Ulteriorly, the present results indicate that supplementation with GF at the 0.8% level significantly increased the villus height in the jejunum and ileum as well as the villus/crypt ratio in the ileum compared with the basal diet (p < 0.05). Compared with the basal diet, 0.4% GF significantly increased Occludin gene expression in ileal mucosa (p < 0.05), 0.6% GF significantly increased ZO-1, Claudin-1, and Occludin gene expression in jejunal mucosa (p < 0.05), and 0.8% GF significantly increased ZO-1 and Occludin gene expression in jejunal mucosa along with Occludin expression in ileal mucosa (p < 0.05). Furthermore, colonic microbiota composition showed that Shannon, observed species, and Chao 1 indices were significantly increased in the 0.8% GF group compared with the basal diet (p < 0.05). At the phylum level, in comparison with the basal diet, the relative abundance of Firmicutes significantly decreased in the 0.4%, 0.6%, and 0.8% GF groups, and Bacteroidetes increased in the 0.8% GF group (p < 0.05). At the genus level, compared with the basal diet, 0.6% and 0.8% GF significantly increased Prevotella abundance, and 0.6% GF significantly decreased Coprococcus abundance (p < 0.05). At the species level, compared with the basal diet, 0.8% GF significantly increased Prevotella copri abundance, and 0.4%, 0.6%, and 0.8% GF significantly decreased Blautia obeum abundance (p < 0.05). In summary, a dietary supplement with 0.8% Gardeniae Fructus powder significantly decreased the F/G and diarrhea rate and improved antioxidant capacity and intestinal barrier function, which may be associated with the improvement of the relative abundance of Prevotella copri. These findings indicate that Gardeniae Fructus powder may be used as a feed additive in swine weaning.